Edge Detection Analysis using Roberts, Sobel, Prewitt and Canny Methods - Utama, Kgs Muhammad Rizky Alditra; Umar, Rusydi; Yudhana, Anton (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2022)
Edge identification in a digital image is overgrowing in line with advances in computer technology for image processing. Edge detection becomes vital in recognizing the object of an image because the edge of the object in the image contains critical information. The information obtained can be either the size or shape of the object in the image, so the edge quality must be good so that the information contained in it is not lost. This study uses edge detection with the Roberts, Sobel, Prewitt, and Canny methods. The assessment method uses visual analysis, PSNR, Histogram, and Contrast. The study shows that the calculation of PSNR on the Roberts method has the highest value, with an average of 44.19 dB. Sobel, Prewitt, and Canny operators have PSNR values above 30 dB to classify it as a good image. The histogram value with the highest value is the Sobel operator, with an average histogram value of 22.06. In contrast, the highest contrast value is the Canny operator has an average contrast value of 5.08. The Roberts and Canny operators have the best image quality.